Integration of islamic banks intothe former USSR, the EU and the USA - Сидоров, Вадим; Гайдей, Никита; Сидоров, Михаил (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
This article analyses the Islamic banks in the countries of the former Soviet Union, the EU and the United States. The basis for the analysis is the integration of Islamic banks into the countries of the former Soviet Union, the EU and the United States. The main features of the integration of Islamic banks in the countries of the former Soviet Union, the EU and the United States, take into account such key elements as «Sharia». The article studies the process of integration of Islamic banks into countries such asRussia, Azerbaijan, Uzbekistan, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, United Kingdom, France, Germany, the United States